Hand hygiene: nurses' adherence after training - João Manuel Garcia do Nascimento Graveto; Rita Isabel Figueira Rebola; Elisabete Amado Fernandes; Paulo Jorge dos Santos Costa
ABSTRACT Objective: Hand hygiene plays a key role in the prevention of healthcare-associated infections. Therefore, this study aims to analyze nurses' adherence to hand hygiene and identify intervention strategies to improve this procedure. Method: Integrative literature review, using the Cochrane methodology, to answer the following question: "What is the level of effectiveness of training in improving nurses' adherence to hand hygiene?". Results: Studies show that nurses' adherence to hand hygiene has increased from 42.9% to 61.4% (p<0.001), or even from 63% to 76% (p<0.005) after a specific training intervention. Conclusion: After training, nurses' adherence to hand hygiene improved, particularly when compared to the other professionals involved. Despite its simplicity, the implementation of a training program and its subsequent follow-up have a positive on nurses' attitudes and adherence to hand hygiene.